Nicaraven Attenuates Postoperative Systemic Inflammatory Responses-Induced Tumor Metastasis - Zhang, Xu (Ann Surg Oncol, 2019)
BACKGROUND: Inflammation has been demonstrated to promote cancer metastasis. Due to the well-known systemic inflammatory responses (SIR) after major surgery, it is critical to investigate and attenuate SIR-induced tumor metastasis of cancer patients suffering surgical procedures. METHODS: C57BL/6 mice were intravenously injected with Lewis lung cancer cells at 6, 24, and 72 h after the induction of intestinal ischemia/reperfusion (I/R) injury. We found that the number of tumor nodules significantly increased in lungs of mice injected with cancer cells at 6 h but not at 24 and 72 h after I/R injury. The administration of nicaraven 30 min before and 24 h after I/R injury effectively attenuated the enhanced tumor metastasis to lungs. Protein array showed the increase of various cytokines in plasma of mice at 6 h after I/R injury, but many of them were attenuated by the administration of nicaraven. Immunostaining indicated the increase of Ly6g-, CD206-, and CD11c-positive inflammatory cells in the lungs, but it was also attenuated by nicaraven administration. CONCLUSIONS: Postoperative SIR-induced tumor metastasis have been clearly evidenced in our experimental model, and the administration of nicaraven may ameliorate the SIR-induced tumor metastasis by suppressing inflammatory responses.